2022
DOI: 10.1021/acssuschemeng.2c04138
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Exchanging Graphenic Nanochannels for Macroscopic Osmotic Energy Harvesting

Abstract: The Gibbs free energy difference between seawater and river water can be tapped by selective ion transport across charged nanochannels, referred to as reverse electrodialysis (RED). However, existing single pore and micro/nanofluidic RED systems have shown poor prospects for scalability and practical implementation. Herein, we present a macroscopic RED system, utilizing a cation-selective membrane or an anion-selective membrane. The membranes comprise reduced graphene oxide (rGO) nanosheets decorated uniformly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Homogeneous membranes are those containing only one component or with uniform distribution of additives, which are usually obtained by filtration of mixed solutions with different additives. For instance, 0D materials (e.g., nanoparticles , ), 1D materials (e.g., nanowires), and 2D materials (e.g., nanosheets) are added as additives to 2D nanosheets or modified 2D nanosheets with functional groups to form homogeneous membranes. Heterogeneous membranes, on the other hand, involve the assembly of 2D materials and functional materials with a distinct bilayer structure, taking into account their different hydrophilicities, surface charges, pore structures, and other characteristics (Figure ).…”
Section: D Ion-selective Membranes Under Small Test Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Homogeneous membranes are those containing only one component or with uniform distribution of additives, which are usually obtained by filtration of mixed solutions with different additives. For instance, 0D materials (e.g., nanoparticles , ), 1D materials (e.g., nanowires), and 2D materials (e.g., nanosheets) are added as additives to 2D nanosheets or modified 2D nanosheets with functional groups to form homogeneous membranes. Heterogeneous membranes, on the other hand, involve the assembly of 2D materials and functional materials with a distinct bilayer structure, taking into account their different hydrophilicities, surface charges, pore structures, and other characteristics (Figure ).…”
Section: D Ion-selective Membranes Under Small Test Areamentioning
confidence: 99%
“…Last but not least, the filling of functional materials provides the effect of space charge, creating a joint surface-space charge effect to enhance ion transport. In this context, functional materials can be classified into 0D materials (e.g., nanoparticles , ), 1D materials (e.g., nanowires), and 2D materials (e.g., nanosheets , ). Given that modified 2D materials and combinations of 2D materials with 1D materials are the most common approaches, this review will primarily focus on membranes fabricated using these two types of materials for osmotic power conversion.…”
Section: D Ion-selective Membranes Under Small Test Areamentioning
confidence: 99%
“…[ 25 ] In addition to physical structure optimization, membrane performance can be efficiently improved by leveraging the unique interactions between nanoparticles and the matrix material. [ 26 ] For example, both 2D Ti 3 C 2 T x and gold nanoparticles (AuNSs) exhibit excellent photothermal conversion performance, with their complementary localized surface plasmon resonance (LSPR) wavelength ranges of 750–850 and 800–900 nm, respectively, facilitating synergistic photothermal performance. Furthermore, due to their high molar heating rate, the gold particles intercalated into the Ti 3 C 2 T x membrane also provide numerous hot spots in nanochannel.…”
Section: Nanomaterials For Membrane Constructionmentioning
confidence: 99%
“…The core component of RED is composed of selective osmotic membranes, and the fundamental issue with these osmotic membranes lies in their requirement to simultaneous possess high surface charge, high nanochannel density, and a certain degree of mechanical robustness. 19,20 Currently, numerous two-dimensional materials, including graphene, 21 graphene oxide, 22 molybdenum disulde, 23 MXene, 24 and boron nitride, 25 have been engineered for application as osmotic selective membranes in RED. The unique layered structure of two-dimensional materials can serve as nanouidic channels, and the specic regions modied with particular surface charges can form Debye double layers that facilitate ion transport, thus diminishing ion transport resistance while enhancing ion ux.…”
Section: Introductionmentioning
confidence: 99%
“…The application of two-dimensional materials in osmotic selective membranes for the generation of osmotic energy has revealed that electronic effects within nanouidic channels can achieve two-dimensional connement of ions and alter their transport. [21][22][23][24][25][26]28 Based on this, the constraints associated with two-dimensional materials can be effectively solved through the modication of interconnected nanochannels within hydrogel network structures possessing high surface charges. Upon conning ions within these nanochannels, the anions/cations exhibit dramatically distinct properties, driven by the surface charge on the inner channel wall, which induces repulsion of like-charged ions and attraction of counter-ions, causing them to be the primary charge carriers.…”
Section: Introductionmentioning
confidence: 99%